2020
DOI: 10.1038/s41598-020-61947-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Overweight/Obesity on Clinical Outcomes of Patient with Vasospastic Angina: From the Vasospastic Angina in Korea Registry

Abstract: obesity is associated with a high risk of morbidity and mortality in the general population and is a major independent risk factor for cardiovascular disease. We sought to evaluate the effect of overweight/ obesity on clinical outcomes of patients with vasospastic angina (VA) at 1-year follow-up. The VA-KOREA (Vasospastic Angina in Korea) registry was a cohort of 11 centers from 2010 to 2015. The primary endpoint was a composite of cardiac death (cD), new-onset arrhythmia, and acute coronary syndrome (ACS). Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Study data were obtained from a nationwide prospective Vasospastic Angina in Korea (VA-Korea) registry. The study design of VA-Korea has been published previously [6,14,15]. Eleven tertiary hospitals in Korea participated in this registry between May 2010 and June 2015.…”
Section: Study Populationmentioning
confidence: 99%
“…Study data were obtained from a nationwide prospective Vasospastic Angina in Korea (VA-Korea) registry. The study design of VA-Korea has been published previously [6,14,15]. Eleven tertiary hospitals in Korea participated in this registry between May 2010 and June 2015.…”
Section: Study Populationmentioning
confidence: 99%
“…In Australian DMP study, overweight was defined as BMI 25–29.9 kg/m 2 and obesity was defined as BMI >30 kg/m 2 ( 8 ). In the Indian SN-DREAMS-I study, obesity was defined as BMI ≥23 kg/m 2 ( 16 ), which in some studies on the Asian population, was defined as overweight ( 21 , 22 ), referring to both the overweight and the obesity populations. Moreover, the mean BMI of patients included in different studies is also varied due to different populations and races.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical variables that are suggested as long-term prognostic factors in some studies require further investigation to confirm their roles in VSA. [5,9,35,45,46] Age [18][19][20] Obesity [22,30] Sex [16,22,26] Organic stenosis [5,13,17,22,24,37] Smoking [34][35][36]38] Alcohol [29,41] Aspirin [74][75][76][77] Definite spasm [17,52] Long-acting nitrate (harmful) [55,[64][65][66] ** Traditional risk factors [14,18,29] Table 1. Cont.…”
Section: Discussionmentioning
confidence: 99%
“…In the nation-wide prospective registry of patients with VSA in Korea (VA-KOREA registry), overweight or obesity was associated with a lower occurrence of clinical events during a 1-year follow-up of VSA patients compared to patients with normal body weight, and the authors suggested the existence of an “obesity paradox” in VSA [ 30 ]. Kim et al showed that obesity (body mass index ≥ 25 kg/m 2 ) was associated with a better prognosis in female VSA patients; however, this association was not observed in male VSA patients [ 31 ].…”
Section: Factors Associated With Long-term Prognosis Of Vsamentioning
confidence: 99%